LncRNA DANCR restrained the survival of mycobacterium tuberculosis H37Ra by sponging miR-1301-3p/miR-5194 - Qu, Yuliang; Jiang, Dan; Liu, Minjuan; Wang, Hongxia; Xu, Tao; Zhou, Haijin; Huang, Minlan; Shu, Weitong; Xu, Guangxian (Frontiers in Microbiology, 2023)
Tuberculosis is a world-wide contagion caused by Mycobacterium tuberculosis (MTB). MTB can live within macrophages and thus results in long term latent infection. Autophagy plays important roles in defending against pathogen invasion. In recent years, an extensive amount of studies have proven that long non-coding RNAs (lncRNAs) play critical roles in modulating autophagy. In our study, the Gene Expression Omnibus (GEO) databases were searched for lncRNAs that are associated with tuberculosis. We found that lncRNA differentiation antagonizing non-protein coding RNA (DANCR) increased in the peripheral blood samples collected from 54 pulmonary tuberculosis patients compared to 23 healthy donors. By constructing DANCR overexpression cells, we analyzed the possible cellular function of DANCR. After analyzing our experiments, it was found that the data revealed that up-regulation of DANCR facilitated expression of signal transducer and activator of transcription 3, autophagy-related 4D cysteine peptides, autophagy-related 5, Ras homolog enriched in brain, and microtubule-associated protein 1A/1B light chain 3 (STAT3, ATG4D, ATG5, RHEB, and LC3, respectively) by sponging miR-1301-3p and miR-5194. Immunofluorescence analysis indicated that DANCR played a positive role in both autophagosome formation and fusion of autolysosomes in macrophages. The colony forming unit (CFU) assay data also showed that the cells overexpressing DANCR were more efficient in eliminating the intracellular H37Ra strain. Consequently, these data suggest that DANCR restrained intracellular survival of M. tuberculosis by promoting autophagy via miR-1301-3p and miR-5194.